PRODUCT MENTOR: PERFORMANCE EVALUATION SYSTEM BASED ON EVALUATION TYPOLOGIES WITH NA EMPHASIS ON PRODUCT MANAGEMENT CAREER (CIPEEX, 2024)
THE RESEARCH FOCUSES ON THE ANALYSIS OF EXISTING EVALUATION METHODS, AIMING TO IDENTIFY GAPS THAT COULD COMPROMISE THE EVALUATION OF PRODUCT MANAGERS. THE PROPOSAL IS TO WORK ON SKILLS BASED ON EVALUATION TYPOLOGIES: ADMISSION, INTEGRATION, PROGRESSION AND DISMISSAL, PROVIDING A MORE ACCURATE ANALYSIS AND CONTRIBUTING TO MORE CONSISTENT TEAM MANAGEMENT. THE METHODOLOGY EMPLOYS BIBLIOGRAPHIC ANALYSIS AND EXPERIMENTAL RESEARCH TO UNDERSTAND THE GAPS AND DEVELOP AN EVALUATION SYSTEM BASED ON TYPOLOGIES. AFTER THE ANALYSIS, SKILLS AND CRITERIA FOR EACH TYPOLOGY ARE DEFINED AND VALIDATED IN A REAL TEAM, WITH ANALYSIS OF RESULTS FOR POSSIBLE IMPROVEMENTS. THE OBJECTIVE IS TO OFFER MORE CONTEXTUALIZED SKILLS MANAGEMENT, WITH POTENTIAL FOR APPLICATION ACROSS DIFFERENT PRODUCT TEAMS.
Keywords: Unievangelica; Skills management; Team management,; Typologies,; Product Managers